The state of Arab philanthropy and the case for change. Issue 5 (3rd July 2016) - Farouky, Naila
ABSTRACT: The Arab Foundations Forum (AFF) has spent the past two years studying the landscape in which the forum functions. AFF, as a membership-based network of philanthropic foundations based in and/or working in the Arab region, is uniquely positioned to canvass the region's donors, grant-makers, and civil society players, and to draw conclusions about the state of the region's philanthropic sector. The overarching conclusion presented in this viewpoint is that there are many challenges, but also ways in which we can help to mitigate these challenges over time. The article points to three key ways in which the philanthropic sector is being challenged.